2011
DOI: 10.1007/s11104-011-0993-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the plant community composition on labile soil organic carbon, soil microbial activity and community structure in semi-natural grassland ecosystems of different productivity

Abstract: Aims The main objective was to describe the effects of plant litter on SOC and on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 44 publications
6
32
0
1
Order By: Relevance
“…Living mulches improve soil physical and chemical properties, and thereby increase the microbial number and activity, which may explain the enhancement of the soil enzyme activity levels [38,42,43]. The diverse effect of living mulches on soil enzyme activities may be related to their various impacts on soil microbial population and community structure [35,44]. Different living mulch types have different effect on soil bacterial activities and community structure had also been proved in this study by the Biolog and T-RFLP methods.…”
Section: Living Mulch Application and Soil Enzyme Activity Levels Insupporting
confidence: 56%
See 1 more Smart Citation
“…Living mulches improve soil physical and chemical properties, and thereby increase the microbial number and activity, which may explain the enhancement of the soil enzyme activity levels [38,42,43]. The diverse effect of living mulches on soil enzyme activities may be related to their various impacts on soil microbial population and community structure [35,44]. Different living mulch types have different effect on soil bacterial activities and community structure had also been proved in this study by the Biolog and T-RFLP methods.…”
Section: Living Mulch Application and Soil Enzyme Activity Levels Insupporting
confidence: 56%
“…The differences in the soil bacterial community structure between the living mulches could be mainly associated with the variation of the soil nutrient levels, mulch function, crop residue components, and root exudates, etc. [43,44]. After the living mulch application, the soil physical and chemical properties were improved [1,2,18].…”
Section: Living Mulch Application and Soil Bacterial Communities In Omentioning
confidence: 99%
“…The positive relationship between labile C and PLFA concentrations supported this point. Similarly, a positive relationship between Gram-negative bacterial PLFAs, actinomycete, protozoan PLFAs, and soil labile C which are decomposed from shoot and root litter was reported by Breulmann et al (2012). Mackie et al (2015) also reported that soil bacterial PLFAs were positively correlated to extractable organic C. Heavy metals could severely restrain microbial growth, because of their known toxicity to microorganisms at high concentrations (Singh et al 2014).…”
Section: Correlations Between Soil Plfas or Metabolic Functions And Cmentioning
confidence: 88%
“…However, to our understanding, the mechanisms of plant rhizosphere regulating soil microbial community structure and function during soil restoration, such as phytoextraction processes, are not well understood. Previous studies have demonstrated that microbial community composition and function can be greatly influenced by soil chemical status such as pH, organic matter, or pollutants (Breulmann et al 2012;Chodak et al 2013;Gartzia-Bengoetxea et al 2016). Relatively few researches have been taken to explore the relationships between microbiological properties and chemical properties in the rhizosphere of hyperaccumulator during phytoextraction.…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 99%
See 1 more Smart Citation